Molecular Prevalence and Phylogenetic Analysis of Anaplasma spp. in Goats from Adana, Türkiye - Gökmen, Tülin Güven; Ütük, Armağan Erdem; Tokgöz, Esra Aslan; Uprak, Nur Sima; Tekin, Afra Sena; Erol, Ufuk; Demir, Pınar Ayvazoğlu; Sezer, Osman; Günaydın, Elçin (MDPI AG, 2025)
Anaplasmosis is a disease in animals that leads to significant economic losses. In addition, the zoonotic potential of vector-borne Anaplasma species is increasing its importance, both around the world and in Türkiye, in particular. The aim of this study was to determine the prevalence and phylogenetic profile of Anaplasma species in goats from the districts of Adana province, Türkiye, via molecular methods. For this purpose, blood samples from 364 goats of various breeds, ages, and genders were collected, and the presence of 55 Anaplasma spp. was determined through the PCR method. Anaplasma ovis was detected in 55 samples (15.1%) and A. phagocytophilum in 11 samples (3%) by Nested-PCR. However, A. capra was not detected. The phylogenetic relationships of A. ovis and A. phagocytophilum were investigated by DNA sequencing of the msp4 and 16S rRNA gene regions. Through sequence analysis in A. phagocytophilum, we identified nine isolates as A. phagocytophilum-like 1 and one isolate as A. phagocytophilum-like 2. Forty-six of the A. ovis isolates were 100% similar to each other. The other 2 isolates were also 100% similar to each other but had a single nucleotide difference from the other 46 isolates. Notably, the isolate identified as A. phagocytophilum-like 2 was detected for the first time in goats in Türkiye.
Keywords: A. capra; A. ovis; Veterinary medicine; goat; SF600-1100; A. phagocytophilum-like 2; Article; A. phagocytophilum-like 1